Dynamic response of a tetrahedral nanomachining machine tool structure. (30th November 2006) - Jackson, Mark J.; Hyde, Luke J.; Robinson, Grant M.; Ahmed, Waqar
The dynamic characteristics of a revolutionary machine tool structure used for machining engineering components at the micro and nanoscales are of paramount importance. Minimising the effects of vibrations at the micro and nanoscale is vital because if a machined workpiece oscillates during the machining process, then an increase in the depth of cut will occur that will reduce the quality of surface finish and the dimensional accuracy of the machined component. The stacking of atoms inspired the design of a new platform structure in order to improve the existing technology, since the goal of the machine is to allow the manipulation of molecules at the nanoscale. The idea for the structure comes from the structural stability afforded by the tetrahedron. The tetrahedral structure is an extremely stable structure and it is hypothesised that the shape could minimise vibrations better than conventional machine tool structures. The reason lies in the way that the structure is kinematically balanced. To explore the hypothesis, an experimental modal analysis established the vibration characteristics of the structure. The modal analysis consisted of measuring the Frequency Response Functions (FRFs) from impact tests to determine the natural frequencies, damping and mode shapes of the structure. A finite element model was compared with the experimental data, thereby validating the model so that it may be used for modelling future changes to the design of next generation machine tools.